Keanekaragaman Ikan di Selatan Papua - Henderite L. Ohee (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
One of zoogeographic provinces of freshwater fish in New Guinea is Southern Province, which almost the same size as Northern Province. This region has high diversity of freshwater fish and also shared 33 species with northern Australia due to land connection in the past. Some endemicity areas with high conservation value are found in this region. The research aims is documenting freshwater fish diversity and its distribution in Southern Papua regencies: Boven Digoel, Mappi, Merauke and Timika. It had been conducted from July to November 2016. Purposive sampling method was used on this research. The fish samples were collected with active method using seine net and those collected with passive method was using gill netts. Fifty species, which consist of 44 natives and 6 introduced species that are part of 29 families and 39 genera were recorded in Timika, Asmat, Boven Digoel, Mappi and Merauke. There was no any dominant fish family found in the survey. Most species found during the survey (60%) has distributed in South New Guinea and Northern Australia. Six (6) introduced species were found spreading in several locations in Southern Papua. Freshwater fish richness in South of Papua and its restricted distribution in the area have showed high conservation value of the area, which should be well managed to avoid fish extinction. Key words: native, endemic, introduced, freshwater fish, South of New Guinea